In Vitro Percutaneous Absorption of Permeation-Enhancing Estrogen Formulations - Guiyun Song; Kendice Ip; Bruce Biundo; Maria Carvalho; A. J. Day; August S. Bassani; Hui Song; Benigno C. Valdez; Daniel Banov (Pharmaceuticals)
Background/Objectives: Hormone Replacement Therapy (HRT) is commonly prescribed to women in need to restore the deficiency of hormones. Estrogens, in particular estradiol (E2) and estriol (E3), are associated with side effects when given orally. As such, estrogen is topically applied on the skin for the delivery of the hormone. The objective of this in vitro study is to evaluate the percutaneous absorption of compounded estradiol 0.06% and bi-est E3/E2 0.1%/0.06% in aqueous and anhydrous proprietary permeation-enhancing bases, in comparison with the commercially available estradiol transdermal gel (ESTROGel®). Methods: The In Vitro Permeation Test (IVPT) was used and validated for the objectives of this study. The strength of estradiol/estriol in five test formulations was determined using Ultra Performance Liquid Chromatography (UPLC). Results: ESTROGel exhibited a rapid increase in the rate of skin absorption of estradiol within 0.5 h post-application. This peak was followed by a rapid decline in flux within 4 h, and then a slower decline by 16 h post-application. The initial rapid increase for ESTROGel was much faster than the rate of the four test compounded formulations, which each exhibited a slow and steady increase in the rate of skin absorption of estradiol with a peak flux within 6 h, and a steady absorption within 16 h of application. Conclusions: The compounded bases facilitated a steady percutaneous absorption of estradiol, without quick peaking or declining, which is one of the desired characteristics in HRT. Compounding pharmacists and practitioners may consider estradiol compounded formulations as a viable option for hormone delivery to patients.